1978
DOI: 10.1080/15287397809529645
|View full text |Cite
|
Sign up to set email alerts
|

Environmental mutagens in urban air particulates

Abstract: A bioassay capable of detecting carcinogenic substances that are associated with the elevated incidence of cancer in the urban environment would be important for epidemiologic and environmental analyses. The feasibility of using the Salmonella mutagenesis system developed by Ames for this purpose has been tested by analyzing Chicago air particulate samples. Active material, as evidenced by enhanced rates of mutation, both in the presence of microsomes and in their absence, is readily extractable from samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Early fetal deaths were observed in mice treated with certain fractions of extracts of airborne particles, indicating mutagenicity to germ cells (Epstein et al, 19721. Transformation of rodent cells in vitro by extracts of airborne particles was demonstrated [Gordon et al, 19731. Data on mutagenicity in vitro have been obtained from the Salmonella/ mammalian microsome (Ames) assay [Ames et al, 19751, which showed that organic extracts of particulates from urban and industrial sources and/or their fractions induce gene reversions in bacteria [see, for example, Commoner et al, 1978; Chrisp and Fisher, 1980; Daisey et al, 1980;Preidecker, 1980;Tokiwa et al, 19801. used alone, because it is a procaryotic test system from which results cannot readily be extrapolated to man and because of inadequacies of endogenous and exogenous metabolic activation, a problem of all in vitro assays. Hughes et a1 [1980] recommended that a battery of bioassays, including the sister chromatid exchange (SCE) assay [Perry and Evans, 1975; Solomon and Bobrow, 1975; Wolff, 19771, should be applied to air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Early fetal deaths were observed in mice treated with certain fractions of extracts of airborne particles, indicating mutagenicity to germ cells (Epstein et al, 19721. Transformation of rodent cells in vitro by extracts of airborne particles was demonstrated [Gordon et al, 19731. Data on mutagenicity in vitro have been obtained from the Salmonella/ mammalian microsome (Ames) assay [Ames et al, 19751, which showed that organic extracts of particulates from urban and industrial sources and/or their fractions induce gene reversions in bacteria [see, for example, Commoner et al, 1978; Chrisp and Fisher, 1980; Daisey et al, 1980;Preidecker, 1980;Tokiwa et al, 19801. used alone, because it is a procaryotic test system from which results cannot readily be extrapolated to man and because of inadequacies of endogenous and exogenous metabolic activation, a problem of all in vitro assays. Hughes et a1 [1980] recommended that a battery of bioassays, including the sister chromatid exchange (SCE) assay [Perry and Evans, 1975; Solomon and Bobrow, 1975; Wolff, 19771, should be applied to air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…3 Weiss 4 also reported a potential correlation between lung cancer death rates, total settled dust, and sulfate concentration in Philadelphia. Coupling this epidemiologic evidence with the report of mutagenicity of air samples in an urban area by Commoner et al 5 further emphasizes the possible role of air pollution in lung cancer.…”
mentioning
confidence: 69%
“…9 This is particularly important in mutagen bioassay since the small particles have been found to have higher content of mutagenic material. 10 Other possible problems are reentrainment into the air stream during arcing and the ozone produced by the corona discharge. Particulate components may be susceptible to alteration by the electrostatic field as well.…”
Section: September 1983mentioning
confidence: 99%